Design and Optimization of EMC Filtering Strategies for DC-DC Converters in Electric Vehicles Applications - Lghazi, Soufiane; M'barki, Zakaria; Mejdoub, Youssef; Senhaji Rhazi, Kaoutar; Ait Salih, Ali (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2026)
The rapid electrification of vehicles intensifies electromagnetic interference (EMI) challenges in DC–DC converters, particularly isolated topologies used for high-voltage to low-voltage energy transfer. High-frequency switching generates common-mode (CM) and differential-mode (DM) conducted noise that threatens compliance with stringent CISPR 25 Class 5 standards. This paper proposes the design, modeling, and evaluation of a compact electromagnetic compatibility (EMC) filter capable of simultaneously suppressing CM and DM emissions in an isolated DC–DC converter for electric vehicle applications. The proposed passive filter combines a CM choke with Y-capacitors, a DM π-filter using X-capacitors and series inductors, and an RC damping branch to avoid resonances. The converter and filter were modeled in LTspice, and conducted emission spectra were evaluated using a Line Impedance Stabilization Network (LISN) with Fast Fourier Transform (FFT) analysis. Simulation results demonstrate that conducted emissions are reduced by about 40 dBµV, ensuring full compliance with CISPR 25 Class 5 limits. The proposed solution offers a cost-effective and practical approach to improve EMC margins and reliability in automotive DC–DC converters. The results presented in this study are based on circuit-level simulations, and experimental validation will be addressed in future work.